Derivation of chicken induced pluripotent stem cells tolerant to Newcastle disease virus-induced lysis through multiple rounds of infection. Issue 1 (December 2016) - Susta, Leonardo; He, Ying; Hutcheson, Jessica; Lu, Yangqing; West, Franklin; Stice, Steven; Yu, Ping; Abdo, Zaid; Afonso, Claudio
Abstract Background Newcastle disease (ND), caused by Newcastle disease virus (NDV), is a devastating disease of poultry and wild birds. ND is prevented by rigorous biocontainment and vaccination. One potential approach to prevent spread of the virus is production of birds that show innate resistance to NDV-caused disease. Induced pluripotent stem cell (iPSC) technology allows adult cells to be reprogrammed into an embryonic stem cell-like state capable of contributing to live offspring and passing on unique traits in a number of species. Recently, iPSC approaches have been successfully applied to avian cells. If chicken induced pluripotent stem cells (ciPSCs) are genetically or epigenetically modified to resist NDV infection, it may be possible to generate ND resistant poultry. There is limited information on the potential of ciPSCs to be infected by NDV, or the capacity of these cells to become resistant to infection. The aim of the present work was to assess the characteristics of the interaction between NDV and ciPSCs, and to develop a selection method that would increase tolerance of these cells to NDV-induced cellular damage. Results Results showed that ciPSCs were permissive to infection with NDV, and susceptible to virus-mediated cell death. Since ciPSCs that survived infection demonstrated the ability to recover quickly, we devised a system to select surviving cells through multiple infection rounds with NDV. ciPSCs that sustained 9 consecutive infections had a statistically significant increase in survival (up to 36 times) compared to never-infected ciPSCs upon NDV infection (tolerant cells). Increased survival was not caused by a loss of permissiveness to NDV replication. RNA sequencing followed by enrichment pathway analysis showed that numerous metabolic pathways where differentially regulated between tolerant and never-infected ciPSCs. Conclusions Results demonstrate that ciPSCs are permissive to NDV infection and become increasingly tolerant to NDV under selective pressure, indicating that this system could be applied to study mechanisms of cellular tolerance to NDV.